2003
DOI: 10.1111/j.1547-5069.2003.00371.x
|View full text |Cite
|
Sign up to set email alerts
|

Issues and Dilemmas in Conducting Research with Vulnerable Home Hospice Participants

Abstract: Loss of potential participants limited this study and hampered effect size. Research with home hospice patients required careful assessment for symptoms that precluded informed consent. Issues with cognition indicated need for a tool to assess mental acuity. Although several participants required assistance, those who completed testing expressed gratitude at being able to contribute information that they believed would benefit others.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
52
0
3

Year Published

2005
2005
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(55 citation statements)
references
References 28 publications
0
52
0
3
Order By: Relevance
“…One study involved focus groups with patients and carers, recordings from which were thematically analysed using an interpretive approach [9]. Two studies considered those who had previously been invited to participate in research projects and analysed retrospectively the reasons why patients participated or declined to participate [5,10]. Not all studies considered all of the themes identified, but all themes were supported in more than one study with the exception of the impact of the views of others that was only considered in one study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study involved focus groups with patients and carers, recordings from which were thematically analysed using an interpretive approach [9]. Two studies considered those who had previously been invited to participate in research projects and analysed retrospectively the reasons why patients participated or declined to participate [5,10]. Not all studies considered all of the themes identified, but all themes were supported in more than one study with the exception of the impact of the views of others that was only considered in one study.…”
Section: Resultsmentioning
confidence: 99%
“…It also provided an opportunity to improve services and support for people in the future [9]. Confirming this, home-hospice participants in the USA expressed gratitude for being able to provide information that might possibly benefit others [10]. Similarly, the most frequently occurring positive theme from a questionnaire asking Scottish hospice patients about participating in research in general was a desire "to help other people" [8].…”
Section: Altruismmentioning
confidence: 89%
“…The power calculation must take into account expected loss of subjects due to death, cognitive changes or symptoms that may prompt a decision to withdraw from the study. This need to oversample has been reported by others [3][4][5]11 and is an important consideration when planning hospice-based research. Based on previous experience, sample size for the REST study was calculated to assure a sufficient number of participants despite an expected 30% study withdrawal rate.…”
mentioning
confidence: 99%
“…Inclusion of an active study arm for massage therapy studies and offering a post-study free massage are strategies to mitigate drop-out rates in massage therapy research. (11).…”
mentioning
confidence: 99%
See 1 more Smart Citation